Hubungan Penyuluhan Pertanian Terhadap Peningkatan Produksi Petani Padi (Kampung Marga Mulya, Distrik Semangga) Kabupaten Merauke - Anggraheni, Naning Dwi; Widyantari, Ineke Nursih; Untari, Untari (MuJAgri: Musamus Journal of Agribusiness, 2021)
This study aims to determine the relationship between agricultural extension workers and farmers' rice production in Marga Mulya Village, Semangga District, Merauke Regency. This research is a descriptive survey research using Likert scale analysis. then analyzed using Pearson Product Moment (PPM) analysis with a total sample of 83 respondents from a total population of 493 people. The results of this study indicate that agricultural extension provides a significant /noticeable to increased the farmers rice production in Marga Mulya Village, it can be seen from the calculation results analysis shows that the value of t = 8.949 is greater than the value of t table = 1.989, while the contribution of the agriculture instructor relationship to increase rice production by 49.7% as determined by HR and the remaining 50.3% is influenced by other variables not included in the model of Pearson Product Moment correlation analysis such as climatic conditions, capital farm management.